2012
DOI: 10.1371/journal.pone.0045982
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Exercise Promotes Human RBC-NOS Activity, NO Production and Deformability through Akt Kinase Pathway

Abstract: BackgroundNitric oxide (NO) produced by nitric oxide synthase (NOS) in human red blood cells (RBCs) was shown to depend on shear stress and to exhibit important biological functions, such as inhibition of platelet activation. In the present study we hypothesized that exercise-induced shear stress stimulates RBC-NOS activation pathways, NO signaling, and deformability of human RBCs.Methods/FindingsFifteen male subjects conducted an exercise test with venous blood sampling before and after running on a treadmill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 54 publications
8
96
1
2
Order By: Relevance
“…These results are in line with a recent report demonstrating that physical exercise positively influences RBC deformability in untrained rodents [4,53]. A recent investigation by Frank Suhr et al indicated that exercise-induced shear stress stimuli activate RBC-NOS via the PI3-kinase/Akt kinase pathway [54]. Activated RBC-NOS generates NO in RBCs, which is mandatory for the beneficial promotion of RBC rheological functions, e.g., deformability [55].…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with a recent report demonstrating that physical exercise positively influences RBC deformability in untrained rodents [4,53]. A recent investigation by Frank Suhr et al indicated that exercise-induced shear stress stimuli activate RBC-NOS via the PI3-kinase/Akt kinase pathway [54]. Activated RBC-NOS generates NO in RBCs, which is mandatory for the beneficial promotion of RBC rheological functions, e.g., deformability [55].…”
Section: Discussionsupporting
confidence: 90%
“…The structure and the interactions between these proteins change during RBC storage due to the degradation of several biochemical parameters, such as SNO and ATP [40][41][42] . The degradation of these biochemical parameters over the RBC storage process has been widely reported, and the depletion of SNO and ATP has been speculated to play important roles in regulating RBCs' mechanical properties 39,[43][44][45] . During RBC storage, the SNO level becomes lower, leading to a lower activity of S-nitrosylation 40 .…”
Section: Rbc Effective Stiffness Increases During Storagementioning
confidence: 99%
“…58,68 Moderate exercise increases antioxidants to counteract oxidative stress, suggesting potential therapeutic benefits with early rehabilitation in the ICU setting. 46,[69][70][71] In CIM there is a preferential loss of myosin relative to actin that cannot be explained merely by immobilization. 72 These structural changes are more likely explained by the direct muscle impairment that underlies CIM and indirect muscle impairment caused by axonal degeneration in CIP.…”
Section: Pathophysiology Of Intensive Care Unit-acquired Weaknessmentioning
confidence: 99%